Representing Parliament: Poets, MPs, and the Rhetoric of Public Reason, 1640-1660 - Tanner, Rory (Université d'Ottawa / University of Ottawa, 2014)
Much recent scholarship celebrates the early modern period for its development of broader public political engagement through printed media and coffeehouse culture. It is the argument of this study that the formation in England under Charles II of a public sphere may be shown to have followed a reassessment of political discourse that began at Westminster during the troubled reign of that king’s father, Charles I. The narrative of parliament’s growth in this era from an “event to an institution,” as one historian describes it, tells of more than opposition to the King on the battlefields of the English Civil War. Parliament-work in the early years of England’s revolutionary decade also set new expectations for rhetorical deliberation as a means of directing policy in the House of Commons. The ideals of discursive politics that were voiced in the Short Parliament (May 1640), and more fully put into practice in the opening session of the Long Parliament (November 1640), were soon also accepted by politically-minded authors and readers outside Westminster. Prose controversy published in print and political poetry that circulated in manuscript both demonstrate that the burgeoning culture of debate outside parliament could still issue “in a parliamentary way.” Such promotion of productive textual engagements eventually constituted a wider, notional assembly, whose participants – citizen readers – were as much a product of deliberate education and fashioning as they were of the “conjuring,” “interpellation,” or “summoning” that recent scholarly vocabulary suggests. Following the spirit of reform in the English parliament, and subsequently developing through the years of partisan political writing that followed, public opinion, like the Commons, established itself in this era as an institution in its own right. These public and private assemblies disseminated the unprecedented amount of parliamentary writing and record-keeping that distinguishes the period under review, and this rich archive provides the literary and historical context for this study.
Keywords: parliament; poetry; public sphere; manuscript studies; John Milton; Thomas Fairfax